Letting the sunshine in on doctor-pharma relationships. (11th October 2011) - Jack, Andrew
Abstract : Drug companies are increasingly obliged to publish details of payments to doctors. The United States is leading the charge, but are we getting the full story in Europe? Andrew Jack reports